An Assessment of the Application of Occupational Ergonomics Principles in the Informal Sector of Harare and Mutare in Zimbabwe - Jerie, Steven (LAR Centre Press, 2022)
A major challenge for the city authorities of Harare and Mutare in Zimbabwe is to come up with clear policies and actions aimed at supporting and nurturing the informal sector as well as improving health and safety in the sector. This study thus aims at assessing the awareness of ergonomics principles in the small-scale enterprises of Harare and Mutare. The level of awareness of ergonomics principles is low in the small scale informal sectors of Harare and Mutare. It was expected that builders, woodworkers and welders would have a higher level of ergonomic principles, but this was not the case. The informal workers are employed in a high-risk sector, but survey results indicated that improving their work environment is not one of their top priorities. The financial situation and the fact that occupational hazards and diseases are not always visible means that their limited resources are allocated to field other than occupational health and safety. Workers in the informal sector are not affected by the traditional employer-employee relationship as that obtains in the formal sector where the employee is obliged to care for the workers occupational health and safety needs. In order to address occupational health and safety discrepancies in the informal sector there is need for change of mindset and this can be catalysed by the local authorities and other organizations. The local authorities can begin by ensuring basic occupational hygiene skills among the informal sector workers so that they may realize their economic potential and hence sustained businesses.